PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN BIOLOGI BERBASIS STEAM PADA SISWA KELAS XI IPA MATERI SISTEM EKSKRESI DI SMA NEGERI 1 DUMOGA TIMUR - Brigitha Lumintang; Rudi A. Repi; Zusje W. M Warouw (SOSCIED, 2023)
The problem in learning Biology is the lack of attention and concentration of students in participating in the teaching and learning process on excretion system material. The learning outcomes of students whose proportion of arrests is only 60% 70% do not reach the predetermined minimum criteria. The use of learning media is still limited to power point so that students are less active. The inactivity of these students was because power point was not able to display three-dimensional images that could clarify excretory system material. So we need learning media in the form of videos. The purpose of this study is to develop learning video media by utilizing STEAM-based learning videos on excretion system material at SMA Negeri 1 Dumoga Timur. The method used is interactive multimedia development research as a learning medium. The results of the Assessment of Content/Material Experts have a proportion of the level of desire for Biological Learning Video Development products of 72%; and presented the results of the Learning Media Expert's Assessment of the level of biological learning video development product offerings, namely 80%.